Principal Leadership Strategy in Developing the Professionalism of Teachers and Education Personnel (Case Study at SMP Negeri 3 Ciruas and SMP Negeri 3 Pontang) - Ropi'ah; Supardi; Atang Suryana (Formosa Journal of Sustainable Research, 2022)
Improving the quality of educational institutions is inseparable from the development of the quality of teachers and education personnel. In facing the challenges of various advances, school principals must have the right and effective strategy in developing the professionalism of teachers and education staff who are able to produce quality students and generations of the nation. This study aims to reveal the principal's leadership strategy in developing the professionalism of teachers and education personnel which is applied at SMP Negeri 3 Ciruas and SMP Negeri 3 Pontang, with a sub focus that includes: (1) Professionalism of teachers and education personnel, (2) Efforts made school principals regarding their duties and functions, (3) Principal leadership strategies in developing the professionalism of teachers and education staff. This type of research is qualitative with a case study approach. The conclusions of this study are: 1). The professionalism of teachers and education personnel is the commitment of teachers and education personnel to carry out tasks according to their abilities and always improve their qualifications and competencies to realize the school's Vision and Mission and National Education Goals. 2) Efforts made by the principals of SMP Negeri 3 Ciruas and SMP Negeri 3 Pontang in developing the professionalism of teachers and education staff are optimizing their duties and functions as Educators, Managers, Administrators, Supervisors, Leaders, Innovators and Motivators. 3) The leadership strategy for the principals of SMP Negeri 3 Ciruas and SMP Negeri 3 Pontang in developing professionalism is a strategy in the form of a human-oriented leadership attitude through a democratic and charismatic attitude